Pengabdian Kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Kantor Brin Kawasan Stasiun Lapangan Stasiun Bumi Parepare - A. Jusriana; Rezki Nurfadillah; Muh. Virgiawan; R. Hamdani; Aspenas Aspenas (JKM: Jurnal Kemitraan Masyarakat, 2024)
Community Service Program (KKN) is a form of student service to the community that aims to apply knowledge and technology in real life. This program serves as a means for students to gain hands-on experience in solving problems within the community, specifically in the area of the BRIN Remote Sensing Office in Parepare. The activities focus on improving the office facility database, which supports office effectiveness in spatial planning management, impacting the quality of office services, and offering innovative solutions for environmental issues, especially waste management in the surrounding area. The activities are conducted in collaboration with government offices and involve active participation from the local community, aligning with the university's mission to create a responsive generation. The implementation of this KKN refers to Law No. 12 of 2012 on Higher Education, which emphasizes the Tri Dharma of Higher Education: education, research, and community service. Within this framework, the KKN program is a form of community service expected to make a tangible contribution to local development, particularly in environmental management.